Causality Investigation Of The Relationship Between Workplace Spirituality And Self-Esteem On Intention To Stay In Work Engagement Mediation For Teachers Of SMK PGRI And Negeri In Mojokerto Regency, East Java - Elfia Nora; Sopiah Sopiah; Imam Bukhori (Brilliant International Journal Of Management And Tourism, 2023)
Workplace spirituality, self-esteem, and work engagement are things that will shape the intention to stay, including teachers in schools. This study aims to 1) Testing the direct relationship between work spirituality and the intention to remain a teacher of SMK PGRI with the Negeri in Mojokerto Regency, 2) testing the relationship of Self-Esteem to the intention to remain a teacher of SMK PGRI and Negeri in Mojokerto Regency, 3) Testing the relationship between work engagement and intention to stay, 4) Testing the relationship between work spirituality and work engagement in teachers of SMK PGRI and Negeri Mojokerto Regency,5) Testing the relationship of self-esteem to work engagement, 6) Testing the relationship of spirituality in the workplace significantly to Intention to Stay through work engagement, 7) Testing the relationship of Self-esteem significantly to Intention to Stay through work engagement.. This type of quantitative research was conducted on teachers of SMK PGRI and Sooko Negeri, Mojokerto Regency, with a total of 74 teachers. The sampling technique used for this study uses simple random sampling because its characteristics are homogeneous. Analysis using path analysis. The results showed that: : 1) descriptive analysis of workplace spirituality variables is included in the category of high, high self-esteem, rather high work engagement and intention to stay is included in the high category, 2) There is a direct influence between work spirituality on intention to stay in teachers of SMK PGRI and Negeri in Mojokerto Regency, 3) there is an influence of Self-Esteem on intention to stay in teachers of SMK PGRI and Negeri in Mojokerto Regency, 4) there is an influence between work engagement on intention to stay, 5) there is an influence between work spirituality on work engagement in Teachers of SMK PGRI and Negeri Mojokerto Regency, 6) there is an influence of self-esteem on work engagement, 7) workplace spirituality indirectly does not have a significant influence on Intention to Stay through work engagement, 8) Self-esteem indirectly does not have a significant influence on Intention to Stay through work engagement.